Parrot Poll: Animal Mimesis in Daniel Defoe’s Robinson Crusoe - Borgards, Roland (Humanimalia, 2020)
The paper focuses on the famous scene in which Poll the parrot talks to Robinson Crusoe. It gives a close reading, revealing the ambivalence of violence and care in the relation between Robinson and Poll. It expands this ambivalence to a postcolonial approach, and it investigates — with and beyond Derrida — the poetological implications of the parrot's faculty of mimesis.